A Review of Polarization Dependence Applications for Asymmetric Waveguides Vertical Couplers in Compound Semiconductor Indium Phosphide. (21st August 2011) - Lee, Chee-Wei
Abstract : This paper reviews and presents a coherent approach to the design of compact vertical coupler (VC) in InP-based compound semiconductor with variable polarization dependence. As a polarization-independent (PI) coupler, the VC is shown to transfer light with more than 90% efficiency for both transverse-electric (TE) and transverse-magnetic (TM) polarizations. As a polarization-mode splitter (PMS), the VC is shown to preferentially couple TE or TM modes with a contrast ratio of up to 20 dB. We further demonstrate the single-mesa VC, which simplifies the fabrication process and potentially could improve the process yield, and its integration with a multimode interferometer (MMI). The versatility makes the VC a compact and useful input-stage device that not only maximizes input/output coupling efficiency to small active devices but also provides a degree of polarization control before the actual device.